Development of software agents to assist in distance learning environment / Mohamad Firdaus Haji Mohemed Abdul Aziz - Mohemed Abdul Aziz (Haji), Mohamad Firdaus (2006)
Now days, there is new learning technique that is more comfortable and contemporary then traditional technique. The students, especially part students do not need to attend the classes, but they can open the online application to get the information by their course tutor. The course tutor can upload the assignments and students have to check and submit them before the due date. The main problem to the course tutors are they have to check one by one, which students do not submit the assignment and which students do not check the assignment. In these cases, course tutor have to do manually and give reminder for student whose performance is at a marginal level. The main objective of implementing this system is to automate the processes of the problem above and software agent is created to do that kind of jobs. According to the testers, function of this software agent is good to help users in specific job and they found this agent can create conclusion for course coordinator and course tutor, based on data given. This project was developed by using an open source tools, which includes Apache web server, PHP and JavaScript as a programming languages and MySql as a relational database management system.